REDUPLIKASI BAHASA MELAYU RIAU DIALEK KUANTAN SINGINGI - Dhea Altha Fino; Alber Alber (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This study aims to describe the forms of reduplication found in the Riau Malay Language of the Kuantan Singingi dialect as an effort to document and preserve the regional language. The study employed a descriptive qualitative method. The data were obtained from native speakers of the Riau Malay Language of the Kuantan Singingi dialect who actively use the language in their daily communication. Data were collected through interviews and note-taking techniques, then analyzed by classifying, describing, and drawing conclusions based on the theory of reduplication. The findings reveal three forms of reduplication, namely full reduplication, partial reduplication, and affixed reduplication. Full reduplication is characterized by the complete repetition of the base form without any phonological changes, partial reduplication involves the repetition of only part of the base form, while affixed reduplication combines reduplication with the addition of affixes. These three forms are still productively used in everyday communication by the speech community. The findings indicate that reduplication remains an active morphological process in the Riau Malay Language of the Kuantan Singingi dialect and enriches the description of reduplication patterns in Riau Malay dialects. This study contributes to the development of regional language morphology studies and provides scientific documentation that can serve as a reference for future linguistic research as well as for the preservation of the Riau Malay Language of the Kuantan Singingi dialect.